Group therapy for adolescents with repeated self harm: randomised controlled trial with economic evaluation. (1st April 2011) - Green, J M; Wood, A J; Kerfoot, M J; Trainor, G; Roberts, C; Rothwell, J; Woodham, A; Ayodeji, E; Barrett, B; Byford, S; Harrington, R
Abstract : Objective To examine the effectiveness and cost-effectiveness of group therapy for self harm in young people. Design Two arm, single (assessor) blinded parallel randomised allocation trial of a group therapy intervention in addition to routine care, compared with routine care alone. Randomisation was by minimisation controlling for baseline frequency of self harm, presence of conduct disorder, depressive disorder, and severity of psychosocial stress. Participants Adolescents aged 12-17 years with at least two past episodes of self harm within the previous 12 months. Exclusion criteria were: not speaking English, low weight anorexia nervosa, acute psychosis, substantial learning difficulties (defined by need for specialist school), current containment in secure care. Setting Eight child and adolescent mental health services in the northwest UK. Interventions Manual based developmental group therapy programme specifically designed for adolescents who harm themselves, with an acute phase over six weekly sessions followed by a booster phase of weekly groups as long as needed. Details of routine care were gathered from participating centres. Main outcome measures Primary outcome was frequency of subsequent repeated episodes of self harm. Secondary outcomes were severity of subsequent self harm, mood disorder, suicidal ideation, and global functioning. Total costs of health, social care, education, and criminal justice sector services, plus family related costs and productivity losses, were recorded. Results 183 adolescents were allocated to each arm (total n=366). Loss to follow-up was low (<4%). On all outcomes the trial cohort as a whole showed significant improvement from baseline to follow-up. On the primary outcome of frequency of self harm, proportional odds ratio of group therapy versus routine care adjusting for relevant baseline variables was 0.99 (95% confidence interval 0.68 to 1.44, P=0.95) at 6 months and 0.88 (0.59 to 1.33, P=0.52) at 1 year. For severity of subsequent self harm the equivalent odds ratios were 0.81 (0.54 to1.20, P=0.29) at 6 months and 0.94 (0.63 to 1.40, P=0.75) at 1 year. Total 1 year costs were higher in the group therapy arm (£21 781) than for routine care (£15 372) but the difference was not significant (95% CI −1416 to 10782, P=0.132). Conclusions The addition of this targeted group therapy programme did not improve self harm outcomes for adolescents who repeatedly self harmed, nor was there evidence of cost effectiveness. The outcomes to end point for the cohort as a whole were better than current clinical expectations. Trial registration ISRCTN 20496110